Islamic Republic of Iran : Selected Issues. (IMF Staff Country Reports; Country Report, 2018)
This Selected Issues paper analyzes the development of domestic government securities market in Iran. The Iranian authorities have intensified efforts to develop a domestic government securities market. The Debt Management Office is fully staffed with front-mid-back office functions. An electronic issuance system and effective custody and settlement systems are in place. A public debt law that identifies the Ministry of Economy and Finance's role as the sole issuer of government securities and requires the preparation and publication of a medium-term debt management strategy, annual borrowing program, and publication of debt and asset data would enhance transparency and provide investors greater assurance about the government's capacity to repay debt and ultimately lower borrowing costs.